Manifesto for a healthy and health-creating society. Issue 10062 (10th December 2016) - Crisp, Nigel; Stuckler, David; Horton, Richard; Adebowale, Victor; Bailey, Sue; Baker, Maureen; Bell, John; Bird, John; Black, Carol; Campbell, Jane; Davies, Janet; Henry, Heather; et al.
Summary: Brexit and the troubled state of the NHS call for re-thinking the UK's approach to health. The EU referendum vote reveals deep social divisions as well as presenting the country with important decisions and negotiations about the future. At the same time, health problems are growing; the NHS faces severe financial constraints and appears to lurch from crisis to crisis, with leaving the European Union likely to exacerbate many problems including staffing issues across the whole sector. However, new scientific developments and digital technology offer societies everywhere massive and unprecedented opportunities for improving health. It is vital for the country that the NHS is able to adopt these discoveries and see them translated into improved patient care and population health, but also that the UK benefits from its capabilities and strengths in these areas.